The Day‐Night Difference and Geomagnetic Activity Variation of Energetic Electron Fluxes in Region of South Atlantic Anomaly - L. Y. Li; S. P. Zhou; S. H. Wei; J. Y. Yang; J. A. Sauvaud; J. J. Berthelier (Space Weather)
Abstract Utilizing the DEMETER observations at 670 km, we examined the day‐night difference of energetic electrons (100–800 keV) in the South Atlantic Anomaly (SAA) region and their dependence on geomagnetic activities in different seasons. Under geomagnetically quiet conditions, the fluxes of higher‐energy electrons (>200 keV) in the dusk and midnight (MLT ~ 19–24 hr) are usually larger than those in the morning (MLT ~ 8–12 hr) in the core region of the SAA (−50 ≤ λ ≤  − 20deg) during the northern and southern summers (21 March 2007 to 23 September 2007 and 23 September 2007 to 21 March 2008). The day‐night difference of energetic electrons in SAA region depends not only on the electron energy but also on the geomagnetic activity levels. Enhanced geomagnetic activities increase the energetic electrons in morning and hence weaken their day‐night difference in the SAA region.